Pretherapeutic dosimetry before 131I therapy of benign thyroid disease - Krohn, T.; Behrendt, F. F.; Heinzel, A.; Müller, B.; Mottaghy, F. M.; Verburg, F. A. (Nuklearmedizin - NuclearMedicine, 2015)
Aim: To compare uptake measurements and different methods for the pretherapeutic determination of the effective thyroidal 131I half life (Teff) to the results of posttherapeutic dosimetric measurements. Patients, methods: Retrospective study of 1538 patients who received their first RIT in our department for autonomous thyroid nodules (ATN), autonomous multinodular goiter (AMG) or Graves' disease (GD) between November 1999 and January 2011. Pretherapeutic measurements were performed at any combination of 24 h, 48 h and 6 days after 131I administration. Post-therapy dosimetric measurements were performed in 12 h intervals until discharge. Teff was determined through monoexponential curve fitting. Results: Pretherapeutic Teff values based on measurements at 24 h and 48 h, 24 h and 6 d, 48 h and 6 d as well as on day 24 h, 48 h and 6 d yielded implausible (< 2 d or > 8 d) values for Teff, in 60.4%, 25.7%, 29.1 and 21.4% of available calculations, respectively. The plausible results showed significant, clinically relevant and sometimes considerable overestimations of Teff. Using empirically determined fixed disease specific Teff values resulted in a better congruence between the pre- and posttherapeutic dosimetry results. 24 h measurements were marginally more accurate than 48 h ones in AMG and GD whereas 48 h measurements were marginally more accurate in ATN; these differences are however not clinically relevant. 6 d measurements are clearly less accurate than those after 24 h or 48 h. Conclusion: In ATN, AMG and GD, pretherapeutic dosimetry can be performed by a single uptake measurement at 24 h or 48 h using a fixed, disease specific value for Teff. Additional later measurements do not yield a further clinically relevant contribution to accuracy of pretherapeutic dosimetry.
Keywords: 131I therapy; benign thyroid disease; dosimetry